OOGENESIS IN THE CANCER CRAB PARTHENOPE LONGIMANUS - Ibrahim, Gaber Ahmed (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Five maturity stages were defined in the ovary of the cancer crab Parthenope longimanus namely immature, early maturing, late maturing, ripe and spent. In immature phase during winter season the ovarian lobules had a great number of oogonia (50 to 60µm in) and few number of previtellogenic oocyte (60 to150µm in). These previtellogenic oocytes had a homogeneous ooplasm. So the winter season can be interpreted as a period of multiplication phase of oogenesis and the primary growth phase began at its end. In spring season the ooplasm of the previtellogenic oocyte (60 to150µm in) became intensely basophilic. These oocytes have undergone two synchronously vital activities. They became follicular and grew gradually in diameter. Opaque granules are deposited in the form of a ring around the nucleus referred to as yolk nucleus. In secondary growth of the oocyte, 150 to 210µm in (vitellogenesis), maturing phase, there were increasing quantities of lipid droplets, peptide linkage, basic proteins, acid MPS, glycogen etc. (see table 2a,b). Yolk bodies (glycoproteins) increased rapidly and replaced the vacuoles located around the periphery of oocyte. The vitelline envelope becomes conspicuous under the follicle cells. Gradually other lipid deposition appeared in the early secondary growth phase and these lipid droplets migrated to the periphery of ooplasm. In ripe phase, during summer season the full-grown oocytes have reached their maximum diameter, 180 to 220µm. The thickness of the vitelline envelope gradually increased. This indicated that the chorion is formed around the oocyte during the process of vacuolization of the follicle epithelium. In spent phase, during autumn the ovaries appeared flaccid, translucent and greatly reduced. The Post-vitellogenic oocyte is characterized by a homogenous ooplasm and the yolk material accepted a clear blue hue with the different triple stains applied. The ooplasm of the previtellogenic oocyte contained ribosomes, mitochondria, Golgi complex, and cisternae of the granular endoplasmic reticulum. In vitellogenic oocytes, the abundance of the endoplasmic reticulum is a particularly striking feature. The Golgi complex consisted of a variable number of stacked cisternae. As vitellogenesis proceeded, the oocyte surface became irregular with the formation of microvilli and micropinocytotic vesicles. A dense granular material present between the follicular cells and the oocyte appeared as detached vesicles in the cortical ooplasm. The number of the different stages of oocyte development has been counted per ovary in the four seasons of the year. This counting has been made in three crabs` ovaries per season. All data were tabulated and have been compared using a 1-way ANOVA (p < 0.05), with the oocyte stages of maturity as a fixed factor.Turkey`s Multiple Comparison test has been applied to compare the ratio of oocyte developmental stages along the year.